2018
DOI: 10.3390/app9010058
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Laser Linewidth on the Brillouin Shift Frequency Accuracy of BOTDR

Abstract: This paper analyzes the influence of laser linewidth on the measurement accuracy of a frequency-scanning Brillouin optical time domain reflectometer (FS-BOTDR), allowing for both the width of Brillouin gain spectrum and the signal-to-noise ratio (SNR) of the BOTDR system. The measurement accuracy of the Brillouin frequency shift (BFS) is theoretically investigated versus the duration of the probe pulse and the linewidth of the laser source, by numerically simulating how a FS-BOTDR works and evaluating the Bril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Only 3 km of fiber was used to measure a linewidth of 150 Hz. In 2018, Bai [58] successfully measured a laser with a linewidth of 98 Hz using the CDSPST method with a fiber delay of 2,950 m. In 2019, He [59] reported a linewidth demodulation scheme that achieved linewidth measurement by demodulating the coherent envelope of a short-delay self-heterodyne interference spectrum, and used this method to demodulate a 2.53-kHz linewidth. In 2020, Wang [60] reported a dual-parameter acquisition method and used it to calculate a 458-Hz linewidth by obtaining the frequency difference and amplitude difference of the coherence envelope.…”
Section: Delayed Self-heterodyne Interferometric Detectionmentioning
confidence: 99%
“…Only 3 km of fiber was used to measure a linewidth of 150 Hz. In 2018, Bai [58] successfully measured a laser with a linewidth of 98 Hz using the CDSPST method with a fiber delay of 2,950 m. In 2019, He [59] reported a linewidth demodulation scheme that achieved linewidth measurement by demodulating the coherent envelope of a short-delay self-heterodyne interference spectrum, and used this method to demodulate a 2.53-kHz linewidth. In 2020, Wang [60] reported a dual-parameter acquisition method and used it to calculate a 458-Hz linewidth by obtaining the frequency difference and amplitude difference of the coherence envelope.…”
Section: Delayed Self-heterodyne Interferometric Detectionmentioning
confidence: 99%
“…The experimental results indicated that the BFS accuracy improves with the laser linewidth narrowing. However, the BFS accuracy will deteriorate when the laser linewidth decreases to a certain value (reported as 98 Hz in [47]), which may arise from the increasing coherent Rayleigh noise (CRN) related closely with the narrowing linewidth. The above reports will be helpful to choose an appropriate laser for BOTDR.…”
Section: Performance Improvement Of Botdrsmentioning
confidence: 99%